"Tambor de crioula" como uma ferramenta pedagógica para a valorização da cultura imaterial da região de Axixá-MA: saberes, memórias e identidade - Honorato, Luciana Maria de Lima (2024)
The Tambor de Crioula is recognized as intangible cultural heritage in Brazil, supported by the Federal Constitution of 1988, and was inscribed in the Book of Forms of Expression in 2007 by the National Institute of Historic and Artistic Heritage (IPHAN). Therefore, this research presents an approach to the Tambor de Crioula as intangible cultural heritage: reflections on the categories of knowledge, memory, and identity. It also discusses popular culture as cultural heritage and the dance of Tambor de Crioula. In this context, the main objective of this research is to investigate how popular culture can interact with identity discourses in the educational process, focusing on the Tambor de Crioula from the state of Maranhão, specifically in the municipality of Axixá, located in the Munim region, in order to enrich the knowledge field of high school students. Therefore, it was essential to develop bibliographic research emphasizing these categories and their relationships with Tambor de Crioula, based on the analysis of texts already produced by literature such as articles, theses, dissertations, and other printed or virtual texts, as well as official documents and legislation. Additionally, part of this study focuses on field research that was carried out with the aim of collecting significant data through questionnaires and interviews, both with participants from two existing Tambor de Crioula groups in the municipality of Axixá and with high school students from the State Institute of Education, Science and Technology of Maranhão (IEMA). The Educational Product resulting from this study is the short film "The Weaves of Tambor," which was also produced in Axixá Maranhão. The relevance of this theme is associated with encouraging the continuity of an intangible heritage so important for the culture not only of Axixá but also for all of Maranhão.